In Silico Interaction of Select Cardiovascular Drugs with the Developmental Signal Pathway Pax3 - Sarah T. Al-Saray ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Paired Box 3 Pax3 is a pivotal protein in embryogenesis. This study computationally examines the interaction between twenty cardiovascular drugs and Pax3. Many of these drugs can cross the placenta, suggesting their potential influence on embryonic safety during pregnancy. This investigation is crucial due to Pax3’s central role in embryogenesis. Methods: The Zinc 15 database was utilized to extract the 3D chemical structures of the selected drug molecules, while the Pax3 protein was obtained from the Protein Data Bank. Subsequently, the structures of both the molecules and the protein were prepared, and the docking process was conducted using Discovery Studio and the Virtual Screening Tool Python Prescription. Results: The majority of the drugs exhibited a propensity for protein binding, with affinity values between them and the Pax3 protein ranging from (-8.3) to (-4.8). Only six of them displayed weak affinities below (-6). The findings unveiled that all of these drugs engaged in varied bonding with amino acids situated within the protein’s active site. Furthermore, most of them formed both conventional and unconventional hydrogen bonds with the protein’s amino acids. Conclusion: These findings highlight intricate interactions between cardiovascular drugs and Pax3 protein. Notably, fetal health in pregnant women using these drugs during pregnancy appears inversely related to their interaction with Pax3. This correlation accounts for both the strength and precision of binding. Consequently, among the studied drugs, Losartan appears safer for fetal development compared to Spironolactone and Ouabain.